1980
DOI: 10.1515/znc-1980-1-202
|View full text |Cite
|
Sign up to set email alerts
|

A Spectroscopic Study on p-Hydroxyphenylpyruvic Acid. Keto-Enol Tautomerism and Stability of Its Complex with Fe+3 Ions

Abstract: Abstract1H-, 13C -NMR , IR, UV-Vis, and MS spectra of p-hydroxyphenylpyruvic acid (pH PPA) have been recorded and fully interpreted.pHPPA exists in solution as a mixture of interconverting forms: keto, hydrated keto and only one enol tautomer to which the Z configuration has been assigned according to the value (3.7 Hz) of the vicinal IH-C = C-13COOH coupling constant.In organic solvents the enol isomer is far more stable whereas in aqueous solutions the keto form predominates. The tautomeric equilibrium is pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
4
11
0
Order By: Relevance
“…3A and B). The co-occurrence of such tautomeric forms has indeed been reported for 4HPP [13,15]. In organic solvents, hence in our I H-NMR analysis, the enol form is far more stable, whereas in aqueous solution the keto form predominates [13].…”
Section: Identi¢cation Of the Reaction Productssupporting
confidence: 79%
See 1 more Smart Citation
“…3A and B). The co-occurrence of such tautomeric forms has indeed been reported for 4HPP [13,15]. In organic solvents, hence in our I H-NMR analysis, the enol form is far more stable, whereas in aqueous solution the keto form predominates [13].…”
Section: Identi¢cation Of the Reaction Productssupporting
confidence: 79%
“…Both isolated compounds showed molecular ions at m/z 247 (M-1) as expected for prenylated 4HPP (Mr 248). Fragmentation was similar to that of 4HPP [13]: m/z (relative intensity): 247 (M-1, 100), 203 (7), 201 (3), 175 (69).…”
Section: Mass 1 H-nmr and Noe Spectramentioning
confidence: 70%
“…On the other hand, a protophilic solvent, such as water and HCl, would reduce the enol formation due to the ionization of PPA. [3][4][5][6]10 Upon considering the influence of a solvent on the keto-enol tautomerism on the basis of the Onsager model, 14 the tautomer should favor its existence in the more polar isomer, i.e., the keto one as the polarity of a solvent increases. 15 It can thereore be understood that the keto form is more stable than the enol one in another solvent, such as water and HCl, [3][4][5][6]10 while the enol form becomes predominant in the DMSO solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Many spectroscopic studies, ultra violet (UV), infrared (IR), Raman and nuclear magnetic resonance (NMR) studies, have been reported on the keto-enol tautomerism [3][4][5][6][7][8][9][10][11][12] and conformation 6,9,10,12,13 of PA and PPA. These many investigations have revealed that these compounds exist as equilibrium mixtures consisting of the keto and enol forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation